Performance Evaluation of Hard Rock TBMs considering Operational and Rock Conditions - Xiaoyang Zou; Hui Zheng; Yongzhen Mi (Shock and Vibration)
This paper focuses on studying the correlations of the performance of hard rock tunnel boring machines (TBMs) with operational and rock conditions. Firstly, a rigid-flexible coupled multibody dynamic model of an opening hard rock TBM is established for the analysis of its vibration. Then four performance indexes including mean vibration energy dissipation rate, dynamic specific energy (DSE), disc cutter wear rate, and load sharing coefficient are introduced and formulated, respectively, for evaluating the vibration level, excavation energy efficiency, cutter’s vulnerability to wear, and load transmission performance of cutterhead driving system of the TBM. Finally, numerical simulation results of the TBM tunneling performance evaluation are obtained and validated by on-site vibration measurement and tunneling data collection. It is found that operational and rock conditions exert important impact on TBM vibration level, excavation energy efficiency, and structure damage. When the type of rock to be cut changes from soft to hard with operational parameters held constant, TBM performance evaluated by these three indexes deteriorates significantly, and both the decrease of excavation energy efficiency and the increase of cutter wear rate caused by TBM vibration are obvious. This study provides the foundation for a more comprehensive evaluation of TBM performance in actual tunneling process.